The Macroeconomic Costs of Conflict - Novta, Natalija (IMF Working Papers; Working Paper, 2020)
Macroeconomic costs of conflict are generally very large, with GDP per capita about 28 percent lower ten years after conflict onset. This is overwhelmingly driven by private consumption, which falls by 25 percent ten years after conflict onset. Conflict is also associated with dramatic declines in official trade, with exports (imports) estimated to be 58 (34) percent lower ten years after conflict onset. The onset of conflict often also induces significant refugee outflows to neighboring non-advanced countries in the short run, and relatively small but very persistent refugee outflows to advanced countries over the long run. Finally, we stress that conflict should be defined in terms of the number of people killed relative to the total population. The traditional definition of conflict-based on the absolute number of deaths-skews the sample toward low-intensity conflicts in large countries, thereby understating the negative effects of conflict from a macroeconomic perspective.